Bibliometric Mapping of Green Economy in Development - Darmawansyah, Trisna Taufik; Aguspriyan, Yani; Masykuroh, Nihayatul; Sudirja, Dede; Setiadi, Rezki Metha; Surahman, Surahman; Aini, Asti (Journal of Education on Social Science (JESS), 2024)
This research presents a bibliometric analysis of the term "Green Economy on Development" in journals indexed by Scopus, using the VOSviewer and Biblioshiny tools. The main objective is to map research trends, identify keywords, collaborate between researchers, and geographically distribute publications related to the green economy in the development context. The methodology includes data collection from the Scopus database, bibliometric network analysis, and visualization with VOSviewer to assess inter-keyword relationships and collaboration patterns. Additionally, Biblioshiny is used for statistical and temporal analysis of publication trends. Search results found 5282 articles related to green economics. The article "Green innovation and organizational performance: The influence of big data and the moderating roles of management commitment and HR practices " is the most cited, with 648 citations since its publication in 2019. The results show that research on the green economy has increased significantly recently, focusing on sustainability, renewable energy and environmental policy. Collaboration analysis shows a robust international network between institutions and researchers. This study provides valuable insights for researchers and policymakers regarding the Development and directions of green economy research and highlights the importance of global cooperation in achieving sustainable development goals.